Oxygen insufflation via the working channel during tracheal intubation guided by a flexible optical scope and benefits, dangers, and future of the method: a narrative review - Alexandre Garioud; Michael Seltz Kristensen (BJA Open)
Summary: When performing tracheal intubation guided by a flexible optical scope, the operator may lose the anatomical orientation and hypoxia may occur. Oxygen insufflation through the working channel of the flexible optical scope is used by anaesthetists to prevent blurring of the lens and to prevent hypoxia. However, fatal iatrogenic injuries from this method are reported. Our aim is to review the current literature on oxygen insufflation through the working channel during tracheal intubation guided by a flexible optical scope, to identify its benefits and the source of its dangers, and ultimately to provide a basis for the development of a safer technique. We conducted a literature search of databases, guidelines, and textbooks using search terms related to oxygen insufflation through the working channel during intubation guided by a flexible optical scope. Clinical trials confirm that the technique results in better visibility and better oxygenation during intubation. Gastric rupture and pneumothorax were the most frequent types of injury. We identified that oxygen insufflation without pressure limitation during accidental misplacement of the flexible optical scope in the oesophagus, deep in the lower airways, or via a tear of the airway mucosa was the cause of barotrauma. We conclude that a delivered pressure below 40 cm H2O will likely carry a low risk of serious adverse outcomes. The technique in its current form seems unsafe, and future research should aim at developing a system that delivers oxygen at pressures respecting gastric and airway physiologic pressure thresholds with a flow sufficient to obtain the documented advantages of the technique.